Expression of beta defensins 1, 3 and 4 in chorioamniotic membranes of preterm pregnancies complicated by chorioamnionitis - Polettini, Jossimara [UNESP]; Takitane, Juliana [UNESP]; Peraçoli, José Carlos [UNESP]; Silva, Marcia Guimarães da [UNESP] (Elsevier B.V., 2011)
Objective: To quantify the expression of human beta-defensins (HBDs) 1, 3 and 4 in chorioamniotic membranes in pregnancies complicated by prematurity associated with histologic chorioamnionitis.Study design: The study group included 23 fragments of chorioamniotic membranes with histologic chorioamnionitis from women with preterm premature rupture of membranes (PPROM) and preterm labor (PTL) with intact membranes, who had preterm deliveries. As a control group, 30 chorioamniotic membranes without chorioamnionitis at the same gestational age as those in the study group were included. Chorioamniotic membranes were collected for histopathological analyses, and HBD mRNA expression quantification was analyzed by real time PCR. Comparisons were performed using the Mann-Whitney or Kruskal-Wallis tests and all the women were informed and provided written consent.Results: The expression of HBDs mRNA in the fetal membranes was similar in patients without histologic chorioamnionitis (HBD1: 0.7-fold, HBD3: 0.9-fold, HBD4: 0.3-fold) compared to patients with chorioamnionitis (HBD1: 1.1-fold, HBD3: 0.9-fold, HBD4: 0.4-fold; p > 0.05). Regarding the gestational complications that resulted in premature delivery, PPROM or PTL, the relative quantification of HBD1. HBD3 and HBD4 showed no statistically significant differences in either the absence or presence of chorioamnionitis. Among patients with histologic chorioamnionitis, patients with PPROM (HBD1: 2.7-fold, HBD3: 0.3-fold, HBD4: 0.7-fold) presented similar mRNA expression to those with PTL (HBD1: 0.7-fold, HBD3: 1.2-fold, HBD4: 0.13-fold; p > 0.05).Conclusions: Chorioamniotic membranes are sources of beta defensins 1,3 and 4; however, considering the sample size and the methodology applied, mRNA concentrations were not related to the presence of histologic chorioamnionitis. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chorioamniotic membranes; Chorioamnionitis; Defensins; Preterm delivery; Real time PCR